2021
DOI: 10.3390/nu13113992
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Changes of the High-Fat Diet-Induced Gut Microbiota upon Consumption of Common Pulses

Abstract: The gut microbiome is involved in the host’s metabolism, development, and immunity, which translates to measurable impacts on disease risk and overall health. Emerging evidence supports pulses, i.e., grain legumes, as underutilized nutrient-dense, culinarily versatile, and sustainable staple foods that promote health benefits through modulating the gut microbiota. Herein, the effects of pulse consumption on microbial composition in the cecal content of mice were assessed. Male mice were fed an obesogenic diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 65 publications
3
33
0
Order By: Relevance
“…As discussed in [ 15 ], incorporating pulses into the diet can improve the quality of food patterns, and population data have reported reduced occurrences of diseases associated with metabolic dysfunction in high pulse consumers [ 16 , 17 , 18 ]. These reports are consistent with our findings that pulse consumption has an anti-obesogenic activity in rodent models of polygenic and dietary-induced obesity, including effects on liver lipid metabolism [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, the minimal pulse dose required to elicit discernible effects on the hepatic phenotype, the impact of biological sex, and underlying molecular mechanisms have not been extensively elucidated.…”
Section: Introductionsupporting
confidence: 93%
“…As discussed in [ 15 ], incorporating pulses into the diet can improve the quality of food patterns, and population data have reported reduced occurrences of diseases associated with metabolic dysfunction in high pulse consumers [ 16 , 17 , 18 ]. These reports are consistent with our findings that pulse consumption has an anti-obesogenic activity in rodent models of polygenic and dietary-induced obesity, including effects on liver lipid metabolism [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, the minimal pulse dose required to elicit discernible effects on the hepatic phenotype, the impact of biological sex, and underlying molecular mechanisms have not been extensively elucidated.…”
Section: Introductionsupporting
confidence: 93%
“…Then, mice were subjected to our previously validated gut depletion and cleansing procedure to eradicate the gut microbiota (12,19). Briefly, the gut-cleansing procedure included a 4-day microbial-depletion treatment with a broad-spectrum antibiotic cocktail [containing ampicillin (1 g), Metronidazole (7)(8)(9)(10)(11) (1 g), S2). We have previously shown that these four pulses, out of 18 different pulses, retain a considerable proportion of RS pre-and post-cooking and lead to the production of short-chain fatty acids (SCFAs) production by human gut microbiota in-vitro (11,22).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Among many pulse varieties grown worldwide, chickpea, dry peas, lentils and dry beans, including black-eyed peas, pinto beans and kidney beans, are some of the most widely consumed pulses in the United States ( 7 ). Collectively, the consumption of whole pulses has been shown to attenuate the risk of chronic diseases by reducing the levels of post-prandial blood glucose, plasma levels of low-density lipoprotein cholesterol, and blood pressure; however, the underlying beneficial mechanisms of whole pulses and/or their constituents on host physiology and gut microbiome in aging milieus remain largely unexplored ( 8 , 9 ). One such pulse-derived dietary fiber worth exploring is the resistant starch (RS), which remains indigestible in the upper gastrointestinal tract and is finally metabolized by intestinal microbes in the large bowel, thereby promoting gut and metabolic health ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, there is sufficient variation at the level of cultivar to identify cultivars with specific fiber subfraction characteristics, although the argument can be made that more information is needed to guide such choices. Emergent areas include how cooking time is impacted by various fiber fractions, whether protein digestibility or content is related to specific fiber fractions, and relative importance of the prebiotic activity of each fraction for gut health (Mongeau et al, 1989 ; Lutsiv et al, 2021 ; Sadohara et al, 2022 ). With such guidance, the opportunity would exist for plant breeders to select cultivars for either IDF or SDF in a breeding program.…”
Section: Discussionmentioning
confidence: 99%